Optimizing Legal Awareness and Critical Thinking Education Through Moot Court Simulation - Belladonna, Aprillio Poppy; Hidayah, Yayuk; Tripuspita, Neneng (Manunggal Halim Jaya, 2025)
This study examines the optimization of legal awareness and critical thinking skills through trial simulations (moot courts) among Pancasila and Citizenship Education (PPKn) students at STKIP Pasundan Cimahi. Using a case study method, this study aims to evaluate how the implementation of moot courts can improve students' legal understanding and critical thinking skills in the context of legal education. The case study method is applied by observing and analyzing student participation in moot court activities. Data were collected through direct observation, interviews, and questionnaires involving students and lecturers. The main focus of this study was to identify changes in legal awareness, level of involvement, and development of critical thinking skills before and after participating in trial simulations. The results showed that participation in moot courts significantly increased students' legal awareness and encouraged the development of critical thinking skills. Students showed a better understanding of legal principles and their practical applications in trial situations. In addition, active involvement in this simulation provided direct experience that enriched their legal knowledge and strengthened their analytical and argumentative skills. This study concludes that moot court is an effective method to improve legal awareness and critical thinking skills among PPKn students, and recommends further integration of this method in higher legal education curricula.